Ekati Diamond Mine, NT -- photograph ... - Seale, Linda N. (University of Alberta Library, 2001)
Aerial view of the open pit Ekati Diamond Mine, 300 km northeast of Yellowknife, NT. Note the snow and ice cover in late June (2001). ...